THE ROLE OF ENSEMBLE PLAYING IN PIANO LESSONS - Nilufar Khudoykulova (Web of Journals Publishing, 2025)
This article examines the history of the origin and characteristics of the piano ensemble, which has a significant impact on musical education, the spiritual and intellectual potential of young people, including the piano duet and piano ensemble, six-and eight-stringed piano ensembles, as well as composers who have created in this genre.
Keywords: Musical education, piano duet, prima, second, trio, quartet, quintet, performance program, ensemble, agogics, pedal, quartet, physiological state.